A Measurement-Based Form of the Out-of-Place Quantum Carry Lookhead Adder - A Trisetyarso; R Van Meter; K M Itoh (Jurnal Otomasi Kontrol dan Instrumentasi, 2009)
We present the design of aquantum carry-lookahead adder using measurement-based quantum computation.The quantum carry-lookahead adder (QCLA) is faster than aquantum ripple-carry adder; QCLA has logarithmic depth while ripple adders have linear depth. Our design is evaluated in terms of number of time steps, number of measurements, the total number of qubits used and the number of successful clustering operations required. Keyword : Quantum Carry-Lookahead Adder, Cluster-State Computation